Cloning and Expression of Luteinizing Hormone Subunits in Chinese Hamster Ovary Cell Line - Soleimanifar, Zeinab; Bandehpour, Mojgan; Kazemi, Bahram (Novelty in Biomedicine, 2016)
Background: Luteinizing hormone (LH) was secreted by the stimulating cells of the testes and ovaries in the anterior pituitary gland. The application of this hormone is in the treatment of men and women with infertility and amenorrhea respectively. Materials and Methods: In the present study the alpha and beta subunits of human LH gene were cloned into the pEGFP-N1 expression vector and produced the recombinant LH hormone in Chinese hamster ovary (CHO) eukaryotic system. Results: Alpha and beta subunits of LH hormone were cloned between NheI and BamHI cut sites of pEGFP_N1 expression plasmid and confirmed by PCR. Hormone expression was evaluated in CHO cell line by Western blotting using the specific antibody. Conclusion: Alpha and beta subunits of LH hormone were expressed in CHO cell line perfectly.